The effect and mechanism of cypermethrin-induced hippocampal neurotoxicity as determined by network pharmacology analysis and experimental validation. Issue 2 (20th December 2021) - Li, Jianan; Bi, Haoran
ABSTRACT: Cypermethrin (CMN) is a widely used artificial synthetic pesticide that causes neurotoxicity in the hippocampus. However, the underlying toxicological targets and mechanisms remain unclear. In this study, network pharmacology analysis and in vitro models were integrated to investigate the effect and mechanism of CMN-induced hippocampal neurotoxicity. A total of 88 targets of CMN-induced hippocampal neurotoxicity were predicted. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes enrichment (KEGG) analyses suggested that these targets were related to multiple GO terms and signaling pathways. To further investigate underlying mechanism, the top 10 hub targets (Akt1, Tnf, Ptgs2, Casp3, Igf1, Sirt1, Jun, Cat, Il10, and Bcl2l1) were screened. Furthermore, cell viability and lactate dehydrogenase (LDH) assays demonstrated that CMN was toxic to HT22 cells in a time- and dose-dependent manner. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining revealed that treatment with CMN increased the proportion of apoptotic cells. In addition, the real-time quantitative polymerase chain reaction (RT-qPCR) results indicated that CMN altered the mRNA expression levels of most of the hub targets, with the exceptions of Igf1 and Jun. The results demonstrated that multiple targets and signaling pathways were involved in CMN-induced hippocampal neurotoxicity. These findings provided reference values for subsequent studies of the toxicological mechanism of CMN.